The gondoliers - Sullivan, Arthur 1842-1900 (Acorn Media Publishing, 2002)
Set in Italy, this comic opera is a tale of temporarily thwarted love, disguises, confusion and jealousy.
Interpr. u.a.: Eric Shilling [The duke of Plaza-Toro]. Christopher Booth-Jones [Luiz]. Keith Michell [Don Alhambra del Bolero]. Francis Egerton [Marco Palmieri]. Tom McDonnell [Giuseppe Palmieri]. London Symphony Orchestra. Alexander Faris [Dir.]. Ambrosian Chorus. John McCarthy [Choreinstud.]. Dave Heather [Regie]. - Aufn.: 1982. - Beih. mit Libretto in engl. Sprache. - Enth. Bonus-Material
Keywords: Musik; Operas; DVD-Video; Fiction television programs; Opera television programs; Television programs; Love stories; Music - Performance - Feature; Musical films